EMPLOYEE PERFORMANCE OPTIMIZATION: EXPLORING THE IMPACT OF COMMUNICATION SYNERGY, WORK CULTURE, AND COMPETENCY - Alan Budi Kusuma; Dhuha Safria; Frida Aprilia; Purwatiningsih Purwatiningsih (Jurnal Scientia, 2023)
This research investigates the complex relationship between communication, organizational culture, and individual competence in shaping employee performance at the Triwijaya Kedaung convenience store and supermarket. A profound understanding of these factors is crucial in the rapidly evolving digital business era. Employing a quantitative research approach through surveys, this study delineates the dynamics of how effective communication practices, applied work culture, and individual competencies of members contribute to their overall performance. The analysis of collected data aims to reveal the specific relationships and interactions among these variables. Understanding the diverse impacts of communication, work culture, and competence on employee performance is expected to assist these institutions in optimizing their operations, enhancing member satisfaction, and ultimately contributing to their sustained growth and success in the financial sector